From Maputo to Malabo: Public Agricultural Spending and Food Security in Africa - (:unkn) unknown (My University, 2018)
Africa is the world's biggest battleground in the fight against hunger. African governments and the international development community have increasingly focused on finding ways and means to end hunger and ensure the right to food to the continent's burgeoning population. Public spending on agriculture is one such measure. This study examines the role government spending on agriculture has played in enhancing Africa's state of food security during the past 25 years. We examine whether this relationship varies over time and space. We explore various aspects of food security and check whether spending on research and development follows the same patterns as the overall public agriculture spending. We find little evidence of significant beneficial effects of public agricultural spending on food security as a whole. However, food security has improved in countries which spend more on agriculture. Spending on agricultural research and development too has shown a useful impact on Africa's food security. There also exists some evidence in favour of public spending's size and time effects. We conclude that the commitment by African government in the Maputo Declaration to allocate 10% of public spending to agriculture appears to be pertinent. JEL Classifications: 011, 055, Q18
Keywords: African Research